Agave lechuguilla as a potential biomass source in arid areas - Houri, Ahmad (2016)
Biomass productivity presents a challenging problem in arid and semi-arid areas. Despite a large need for energy in the form of solid biomass, liquid fuel or needs for animal feed, these regions remain largely unproductive. A convenient way to overcome this challenge is to utilize plants with high water-use efficiency. Agave lechuguilla is an example of a highly productive (3.8 tons ha-1 yr-1 ) desert plant that holds the potential for producing biomass with minimal water resources. For this purpose, a global suitability map has been developed showing areas where this plant can be planted, and its productivity was assessed. A Maxent model was used and was further refined by excluding protected areas and used lands (urban, agriculture, etc.). Productivity assessment provides a good way forward for prioritizing the regional utilization of this plant. This study provides an initial analysis for the use of arid and semi-arid regions for biomass production. Results indicate the potential generation of 93.8 million tons per year of dry biomass if the suitable areas were fully utilized. The analytical method can be readily applied to other potential plant species to optimize the use of certain areas.